Rapid and Accurate Anatomical Localization of Implanted Subdural Electrodes in a Virtual Reality Environment - Serra, Carlo; Huppertz, Hans-Jőrgen; Kockro, R.A.; Grunwald, Thomas; Bozinov, Oliver; Krayenbühl, Niklaus; Bernays, René-Ludwig (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2013)
Background An accurate and rapid anatomical localization of implanted subdural electrodes is essential in the invasive diagnostic process for epilepsy surgery.Objective To demonstrate our experience with a three-dimensional (3D) virtual reality simulation software (Dextroscope®, Bracco Imaging, Milano, Italy) in the postoperative localization of subdural electrodes.Methods Postoperative thin-slice computed tomography (CT) scans were coregistered to preoperative 3D magnetic resonance (MR) images in the Dextroscope environment in 10 patients. Single-electrode contacts were segmented and their positions in relation to specific brain anatomic structures were obtained by 3D reconstruction within the Dextroscope environment. The spatial accuracy was tested by comparing the positions of the electrode contacts as visible in the 3D reconstruction with intraoperative photographs. Image processing time was also recorded.Results The 3D stereoscopic reconstruction provided an accurate representation of the implanted electrodes with highly detailed visualization of the underlying anatomy. The mean absolute difference between 3D reconstruction and intraoperative photographs was 2.4 mm ± 2.2 mm. The processing time to obtain the 3D reconstructions did not exceed 15 minutes.Conclusions The results indicate that the 3D virtual reality simulation software used in our series is a useful tool for rapid and precise localization of subdural electrodes implanted for invasive electroencephalography (EEG) recordings.
Keywords: Dextroscope; subdural; electrodes; epilepsy; neurosurgery